ERCC1 polymorphism and its expression associated with ischemic stroke in Chinese population - Deng, Xiao-Dong; Ke, Jian-Lin; Chen, Tai-Yu; Gao, Qin; Zhao, Zhuo-Lin; Zhang, Wei; Liu, Huan; Xiang, Ming-Liang; Wang, Li-Zhen; Ma, Ying; Liu, Yun (Frontiers in Neurology, 2023)
Background: Excision Repair Cross Complementing Group 1 (ERCC1) was considered as a potential candidate gene for ischemic stroke, and its polymorphisms might be associated with the susceptibility to ischemic stroke. Methods: A total of 513 patients with ischemic stroke and 550 control subjects were recruited. The expression levels of ERCC1 messenger RNA (mRNA) in peripheral blood mononuclear cells and its protein in plasma were detected by quantitative real-time PCR (qPCR) and enzyme-linked immunosorbent assay (ELISA), respectively. Rs3212986 polymorphism of ERCC1 was detected by PCR-restriction fragment length polymorphism (RFLP-PCR) and was confirmed by sequencing. The association between ERCC1 rs3212986 polymorphism or its expression and ischemic stroke was further analyzed. Results: The ERCC1 mRNA level in ischemic stroke patients was lower than that in the control group (P<0.05). However, the ERCC1 protein level in ischemic stroke patients was higher than that in the control group (P<0.05). The A allele of rs3212986 was associated with increased ischemic stroke risk (OR=1.287, 95% CI =1.076-1.540, P=0.006).The association between rs3212986 polymorphism and ischemic stroke susceptibility was founded under recessive model (OR=2.638, 95% CI=1.744-3.989, P<0.001) and additive model (OR=1.309, 95% CI=1.028-1.667, P=0.031), respectively. Similar results were obtained in recessive model (OR=2.015, 95% CI=1.087-3.704, P=0.026) after adjusting for demographics information and other variables. Additionally, the level of ERCC1 mRNA in CC/CA genotype was higher than that in AA genotype (P<0.05). Conclusion: It was suggested that ERCC1 rs3212986 polymorphism was associated with ischemic stroke susceptibility in a Chinese Han population, and A allele of rs3212986 was related to increase ischemic stroke risk. The altered ERCC1 expression level caused by rs3212986 polymorphism might participate in the pathophysiological process of ischemic stroke.